(untitled) (FULafia Journal of Science and Technology, 2019)
Anthropometric study, a method of distinctions among different ethnic groups, is an important element for designing ergonomic products. This cross-sectional study evaluated the variations in body composition of adult women in Yoruba ethnic groups (aw-Yeg) and the adult female anthropometric data used to produce foreign-made wares (F-Mws) imported into Nigeria by some unidentified F-Mws industry. Conducted in two sections, assessments of F-Mws usage and fitness and the measurement of anthropometric data of the aw-Yeg, the primary data was collected from 400 aw-Yeg, in the south-western Nigeria, using structured questionnaires. About 57% of the aw-Yeg had patronized F-Mws within the past two years and 77.5% of them made some adjustments, on the wears prior to use. Some of the affected parts of the wares (reported) include; hip circumference (54%), waist circumference (53%),chest circumference (36%),chest-depth (34%), thigh and mid-thigh circumferences (35%). The study indicated some variations in the anthropometric data of aw-Yeg and the data used to produce the imported wares. Hence, aw-Yeg carried out fitting adjustments on the F-Mws. The 95th percentile anthropometry measurements of an average aw-Yegheight was 64cm, buttock popliteal was 20 cm, hip circumference (50 cm), chest breadth (20 cm) and anterior posterior chest-depth (15 cm),waist circumference (45 cm)among others.The results of this study is relevant to foreign industries who may invest in making products such as gowns, pants, skirt, bra, long or trousers for aw-Yeg in Nigeria.